Analysis of the Application of Blockchain and Artificial Intelligence to Overcome Accounting Fraud in Islamic Banking - Zulhelmi, Tiara; Asih, Vemy Suci; Helmiawan, Muhammad Agreindra (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
Blockchain and Artificial Intelligence (AI) are current technologies that provide increased efficiency and performance for all aspects of human life, especially in the Islamic banking sector. This study aims to analyze the concepts of blockchain and AI in accounting and find out the benefits and opportunities when applied simultaneously to accounting information systems in Islamic banking. This study uses a qualitative approach, with basic-research based research by utilizing data sources in credible published papers. This study explains that blockchain and AI can reduce risk and overcome accounting fraud in accounting information systems in Islamic banking. As well as providing transparency, security guarantees and real time transaction recording.